Prototype Pendeteksi Daerah Rawan Kecelakaan Berbasis Internet of Things - Yankotinu Al Qod'r Jonnata; Fahrudin Mukti Wibowo; Iqsyahiro Kresna A (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2020)
The high number of deaths due to traffic accidents is still a problem for every country where Indonesia ranks third in Asia with 38,279 deaths according to the 2015 Global Status Report on Road Safety. Blackspots scattered in Indonesia has a role in contributing to the death rate, however not all blackspots are equipped with warning signs. Based on these problems then developed a prototype in the form of a device for detecting and website as the central information system of blackspots based Internet of Things. The prototype is designed using an Arduino Uno Rev 3 microcontroller equipped with a GPS module to measure vehicle speed and distance from the setpoint before arriving on blackspots, a GSM module to download blackspots data and upload speed and distance data to the database, and LED components, speakers/buzzer, OLED display to provide notification every time crossing the setpoint of blackspots. The usability testing performance measurement method is used to measure the performance of the device prototype and the black box testing method is used to validate each function of the website system. The results of this research obtained the success rate of the prototype device was 60% with the highest error rate of 19.09% at the 1500m setpoint for speed and 57.98% at 10m setpoint for the distance.